Lista de Publicação em Ciências da Nutrição 1991-1993 - Revista de Nutrição (Revista de Nutrição, 1995)
ADDISON, E.; FORS, M. C.; FACCIO, J. R. R. M. & VANNUCCHI, H. Study of the metabolic nitrogen balance of patients with type II diabetes receiving a Brazilian regional rice and bien diet. Nutrition Research, Elmsford, v. 13, p. 263-273, 1993. ALMEIDA-MURADIAN, L. B. & PENTEADO, M. V. C. Carotenoids and provitamin A value of some Brazilian sweet potato cultivars (lpomoea batatas, Lam.). Revista de Farmácia e Bioquímica da Universidade de São Paulo, São Paulo, v. 22, n. 2, p. 45-54, 1992. _______; ______ & FERREIRA, V. L. P. Relationship between carotenoid content and color parameters of Brazilian sweet potato (lpomoea batatas, Lam.) Revista Española de Ciência y Tecnologia de Alimentos, v. 32, n. 6, p. 611-619, 1992. ALVARENGA, R. C. C.; TENUTA-FILHO, A. Fluoride bioavailability of Antartic krill paste in rats. Boletim da Sociedade Brasileira de Ciência e Tecnologia de Alimentos, Rio de Janeiro, v. 27, n. 2, p.105-110, 1993. ANTUNES, L. A. F.; SOUZA, R.D.N. & SILVA, R. S. da. lntroduction of soy protein in the. production of soft cheese. Joumal of Dairy Science, Champaign, II, v.76, p.141, 1993. (supplement 1). ARÊAS, J. A. G.; ALCOCER, M. J. e. & MOTA, E. M. A. Effect of organic solvent and the lipid content on functionality of bovine lung protein isolates. Food Chemistry, Barking, v. 48, p. 285-290, 1993. __________& WATTS, A. lnteraction of myosin with charged membranes in affected by ATP. Biochemical Society Transactions, London, v. 21, p. 80, 1993. AUED-PIMENTEL, S.; ALMEIDA-GONÇALVES, M. I. & MANCINI FILHO, J. Aplicação da espectroscopia derivada na avaliação da qualidade do azeite de oliva. Ciência e Tenologia de Alimentos, Campinas, v. 13, n. 2, p.100-102, 1993. BASTOS, D. H. M.; DOMENECH, C. H. & ARÊAS, J. A. G. Optimization of extrusion cooking of lung proteins by response surface methodology. lnternational Food Science Technology, V. 26, p. 403-408, 1991. BATISTUTI, J. P.; BARROS, R. M. C. &AREAS, J. A. G. Optimization of extrusion cooking process for chickpea (Cicer arietinum, L) defatted flour by response surface methodology. Journal of Food Science, Chicago, v. 56, p.1695-1698, 1991. BELDA, M. C. R. & OUTRA DE OLIVEIRA, J. E. Novas formas de aprender: análises e tendências. Alimentos e Nutrição, São Paulo, v.4, p. 131-134, 1992. BIANCHI, M. L. P.; SILVA, H. C. & OUTRA DE OLIVEIRA, J. E. Considerações sobre a disponibilidade de ferro dos alimentos. Archivos Latinoamericanos de Nutrición, Guatemala, v. 42, p. 94-100, 1992. BOAVENTURA, G. T. & COZZOLINO, S. M. F. Selenium bioavailability in the regional urban diet of Mato Grosso - Brazil. lnternational Journal of Food Sciences and Nutrition, Chambridge, v. 43, n. 4, p. 223-229, 1993. BOOG, M. C. F. Perspectivas da abordagem holística para a dietética. Revista de Nutrição da PUCCAMP, Campinas, v. 5, n. 1, p. 171-180, 1992. BRASIL, A. L. D.; COELHO, M. R. V.; LOPEZ, F. A. & NÓBREGA, F. J. Gravidez e lactação na adolescência. Revista Paulista de Pediatria, São Paulo, v. 9, n. 3, p. 39-43, 1991. ________; VÍTOLO, M. R.; ANCONA LOPEZ, F. & NÓBREGA, F.J. Fat and protein composition of mature milk in adolescent. Joumal of Adolescent Health Gare, New York, v. 12, p. 365-371, 1991. CABRAL, M. M. V. N. & SGARBIERI, V. C. Hemoglobin repletion in anemie rats fed a new bean cultivar (Phaseolus vulgáris, L) as source of iron. Joumal of Nutritional Science and Vitaminology, Tokyo, V. 38, p.481-491, 1992. CALDAS, E.D. & DOREA, J.G. Cobalt and vitamin 8-12 interralationship in liver of fetuses. The Joumal of Nutritional Biochemistry, Stoneham, v. 3, p. 539-542, 1992. ______; GINE, M. F. & DOREA, J. G. Determination of cobalt in human liver by electrothermal atomic absorption spectrophotometry. Analytica Chimica Acta, Amsterdan, v. 254, p. 113-118, 1991. CAMPOS, M.A. &ARÊAS, J.A.G. Protein nutritional value of extrusion cooking defatted lung flour. Food Chemistry, Barking, v.47, p.61-66, 1993. CARDOSO, M. A.; COLLI, C.; GARCIA, P. B.; FERREIRA, M. U.; PENTEADO, M. V. C. & ANDRADE JUNIOR, H. F. Effect of dietary iron on the course of Plasmodium berghei malaria in young rats. Brazilian Joumal of Medical and Biological Research, Ribeirão Preto, v. 26, n. 12, p. 1297-1303, 1993. ________; FERREIRA, M. U.; CAMARGO, L. M. A. & SZARFARC, S. C. Anemia iron deficiency and malaria in a rural community in Brazilian amazon. European Joumal of Clinicai Nutrition, London, v. 48, p. 326-332, 1993. _______; ________; ________ & _________. Anemia em população de área endêmica de malária, Rondônia (Brasil). Revista de Saúde Pública, São Paulo, V. 26, n. 3, p.161-166, 1992. _________ & TIRAPEGUI, J. O. Serum concentrations of insulin-like growth factor - I (IGF-1) and proteoglycan synthesis rates in young rats: a comparative study between the regional diet of São Paulo state and casein diets. Brazilian Joumal of Medical and Biological Research, Ribeirão Preto, v.25, n.10, p.1009-1013, 1992. CINTRA, R. M. G. C. & COZZOLINO, S. M. F. Selenium bioavailability in a regional diet of São Paulo - Brazil. lntemational Joumal of Food Science and Nutrition, v. 44, p.167-173, 1993. COELHO, L. T.; MARTINS, I. S. & SANNAZZARO, C. A. C. Fibras alimentares e lipoproteicas. LAESIHAES, São Paulo, v.15, n. 85, p. 64-66, 1993. ______ ; SANNAZZARO, C. A. & MARTINS, I. S. Níveis lipêmicos em crianças e adolescentes: detecção e controle. LAESIHAES, São Paulo, v.13, n. 77, p. 28-34, 1992. COELHO, R.G. Considerações sobre as proteínas de feijão. Revista de Nutrição da PUCCAMP, Campinas, v. 4, n.1/2, p.122-145, 1991. CORTIELLA, J.; MARCHINI, J. S.; BRANCH, S.; CHAPMAN, T. E. & YOUNG, V. R. Phenylalanine and tyrosine kinetics in relation to altered protein and phenylalanine and tyrosine intakes in healthy young men. American Joumal of Clinical Nutrition, Bethesda, v. 56, p. 517-525, 1992. COSTA, M. C. O.; QUEIROZ, S. S.; VÍTOLO, M. R. & NÓBREGA, F. J. Estudo do perfil lipídico do colostro de adolescentes mães de recém-nascidos prematuros. Jornal de Pediatria, Rio de Janeiro, V. 67, n. 7/8, p. 231-237, 1991. COSTA, R. S.; JORDÃO JÚNIOR, A. A.; MONTEIRO, J. F.; MENDES, A. C.; REGO, E. M. & MARCHINI, J. S. Avaliação do estado nutricional de pacientes leucêmicos sob quimioterapia. Revista Brasileira de Nutrição Clínica, Porto Alegre, v. 6, n. 2, p. 7, 1991. COZZOLINO, S. M. F.; CINTRA, R. M. G. & PEDROSA, L. F. C. Dieta regional de São Paulo: efeito da suplementação com minerais e vitaminas. Revista de Farmácia e Bioquímica da Universidade de São Paulo, São Paulo, v. 28, n. 2, p. 155-165, 1992. CUNHA, D. F. & VANNUCCHI, H. Aumento dos níveis de ácido úrico sérico: um efeito de nutrição enteral. Medicina, Ribeirão Preto, v. 24, n. 1, p. 3-9, 1991. CUNHA, S. F. C.; BIANCHI, M. L. P.; CUNHA, D. F.; SALGADO, S. M. & OUTRA DE OLIVEIRA, J. E. Ingestão de fibras alimentares em mulheres com constipação intestinal. Arquivos de Gastroenterologia, São Paulo, v. 29, n. 4, p.137-141, 1992. DATTA, P. K.; FIGUEROA, M. O. R. &LAJOLO, F. M. Purification and characterization of two major lectins from Araucaria brasiliensis syn Araucaria angustifolia seeds (pinhão). Plant Physiology, Lancosta, v. 97, p. 856-862, 1991. _____; ____ & ____ . Chemical modification and sugar binding properties of two major lectins from pinhão (Araucaria brasiliensis) seeds. Journal of the Agricultural and Food Chemistry, Washington, DC, v. 41, p. 1851-1855, 1993. DE ZOYSA, I.; REA, M. F. & MARTINES, J. C. Why promote breastfeeding in diarrhoea disease control programmes? Health Policy and Planning, Oxford, v. 6, n. 4, p. 371-379, 1991. DEONIS, M.; MONTEIRO, C. A.; AKRÉ, J. & CLUGSTON, G. The worldwide magnitude of protein-energy malnutrition: an overview from the WHO Global Database on Child Growth. Bulletin of the World Health Organization, Geneva, v. 71, n. 6, p. 703-712, 1993. DESTRO, M. T.; SERRANO, A. M. & KABUKI, D. Y. lsolation of Listeria species from some Brazilian meat and dairy products. Food Contrai, v. 2, n. 2, p.110-112, 1991. _______; ________&_________. Comparasion of two planting media for the isolation of Listeria sp from some Brazilian dairy and meat products. Revista de Microbiologia, São Paulo, v. 23, n. 4, p. 256-259, 1992. DOMENE, S. M. A. & OLIVEIRA, A. C. The use of nitrogen-15 labeling for the assessment of leguminous protein digestibility. Journal of Nutritional Science and Vitaminology, Tokyo, v. 39, n .1 , p. 4 7-53, 1993. DONANGELO, C. M.; TRUGO, N. M. F. & DOREA, J. G. Hepatic reserves of iron, copper and vitamin 8-12 in Brazilian fetuses and infants of different socioeconomic status. Nutrition, London, V. 9, p. 430-432, 1993. DOREA, J. G. Concentration of zinc and copper and metallocalorie ratio in bottle-milks as prepared by poor urban families. Annals of Tropical Paediatrics, Abingdon, v. 12, p. 7-11, 1992 . ______. Is zinc a first limiting nutrient in human milk? Nutrition Research, Elmsford, v. 13, p. 659-666, 1993. ______; COSTA, T. H. M. & MARQUES, A. O. Effects of contraceptive practices on serum and milk zinc. The Joumal of Nutritional Biochemistry, v. 4, p. 86-91, 1993. _______ & FURUMOTO, R. A. V. lnfant feeding practices among poor families of an urban squatter community. Annals of Nutrition and Metabolism, Basel, v. 36, p. 257-264, 1992. DUTRA DE OLIVEIRA, J.E. Aprendendo e ensinando os caminhos da medicina: experiências nacionais e os "novos caminhos" da Harvard. Revista da Associação Médica Brasileira, São Paulo, v. 37, n. 3, p. 127-131, 1991. _______. Malnutrition in developing countries: the challenges to and the responsability of the experts. Proceedings of the Nutrition Society, London, v. 37, p. 1-10, 1991. _______ . Realidades, padrões e perspectivas de programas de pós-graduação. Alimentos e Nutrição, São Paulo, v. 3, p.111-115, 1991. _______ . Diet and body lipid composition: lessons from animal and human experiments. Journal of the American College of Nutrition, Bethesda, v. 11, n. S, p. 60S-62S, 1992. ____ . Novos caminhos para o ensino de alimentos e nutrição. Archivos Latinoamericanos de Nutrición, Guatemala, v. 42, n. 3-s, p.102S-107S, 1992. _____. Educação médica e assistência médica à Faculdade de Medicina do Deserto, Israel. Revista da Associação Médica Brasileira, São Paulo, v. 39, n. 4, p. 194-196, 1993. ______& MARCHINI, J. S. A balanced diet does not have to contain meat. World Health Forum, Geneva, v. 12, n. 3, p. 261, 1991. ____ & _____ . Recent trends in nutritional sciences. Archivos Latinoamericanos Nutrición, Guatemala, v. 42, n. 1, p. 6-8, 1992. FAUSTO, M. A. Vitamina A e câncer. Revista de Nutrição da PUCCAMP, Campinas, v. 4, n. 1/2, p.154-165, 1991. FAVARO, R. M. D.; FERREIRA, J. F.; DESAI, I. D. & DUTRA DE OLIVEIRA, J. E. Studies on fortification of refined soybean oil with all-trans-retinyl palmitate in Brazil: stability during cooking and storage. Joumal of Food Composition and Analysis, San Diego, v. 4, p. 237-244, 1991. ______; MIYASSAKA, C. K.; DESAI, I. D. & OUTRA DE OLIVEIRA, J. E. Evaluation of the effect of heat treatment on biological value of vitamin A fortified soybean oil. Nutrition Research, Elmsford, v. 12, p. 1357-1363, 1992. FERREIRA, J. F.; ARANDA, R. A.; BIANCHI, M. L. P.; DESAI, I. D. & OUTRA DE OLIVEIRA, J. E. Utilização de água potável como veículo de nutrientes: estudos experimentais com ferro. Archivos Latinoamericanos de Nutrición, Guatemala, v. 51, n. 3, p. 400-408, 1991. FILISETTI-COZZI, T. M. C. C. & CARPITA, N. C. Measurement of uronic acid without interference from neutral sugars. Analytical Biochemistry, New York, v. 197, p. 157-162, 1991. ____ & LAJOTO, F. M. Fibra alimentar insolúvel, solúvel e total em alimentos brasileiros. Revista de Farmácia e Bioquímica da Universidade de São Paulo, São Paulo, v. 27, p. 83-89, 1991. FISBERG, M. K.; ANCONA LOPEZ, F.; NÓBREGA, F. J.; VÍTOLO, M. R.; BRASIL, A. L. D.; SILVA, M. P. N.; LIZO, C. L. P.; SCHUSSEL, E.Y.; ESCRIVÃO, A. M. S.; CAMPOS, A. L. R.; MORAES, D. E. B. & SCHMIDT, B. J. lnfantile obesity: a multidisciplinary approach international child health, a digest of current information. lnternational Child Health: A Digest of Current lnformation, Berkeley, v. 4, n. 3, p. 77-82, 1993. FRANCO, B. D. G. M.; GOMES, T. A. T.; JAKABI, M. & MARQUES, L. R. M. Use of probes to detect virulence factor DNA sequences in Escherichia coli strains isolated from foods. lntemational Journal of Food Microbiology, Amsterdam, v. 12, p. 333-338, 1991. _________; LANDGRAF, M.; BRANCHER, I. & GOULARTE, L. Visão geral sobre novos métodos em microbiologia de alimentos. Boletim da Sociedade Brasileira de Ciência e Tecnologia de Alimentos, Rio de Janeiro, v. 26, n. 1, p. 45-52, 1992. FREITAS, O.; PADOVAN, G.; VILELA, L.; SANTOS, J. E.; OUTRA DE OLIVEIRA, J. E. & GREENE, L. Characterization of protein hydrolysates prepared for enteral nutrition. Journal of Agricultural and Food Chemistry, Washington, DC, v. 41, n. 9, p. 1432-1438, 1993. FUZIHARA, T. O. & FRANCO, B. D. G. M. Bactérias patogênicas e bactérias indicadoras de higiene em carne suína comercializada em Santo André, SP. Ciência e Tecnologia de Alimentos, Campinas, v. 13, n. 1, p. 77-88, 1993. GARCIA, E.; LAJOLO, F. M. & SWANSON, B. G. A comparative study of normal and hard-to-cook Brazilian common bean (Phaseolus vulgaris) ultrastructural and histochemical aspects. Food Structure, v.12, p.147-154, 1993. GARCIA, R. W. D. Um enfoque simbólico do comer e da comida nas doenças. Revista de Nutriçao da PUCCAMP, Campinas, v. 5, n.1, p. 70-80, 1992. GENOVESE, M. I. & LAJOLO, F. M. Composition and structural characteristics of isolated soy protein from broken and damaged seeds. Joumal of Food Science, Chicago, v. 58, n. 1., p.148-152, 157, 1993. ______& _____ . Utilização do método colo-rimétrico de McCarthy e Sullivan para a determinação de metionina biodisponível em proteínas de feijão (Phaseolus vulgaris). Arquivos de Biologia e Tecnologia, Curitiba, v.36, n.3, p.545-566, 1993. GOLDANI, L. Z.; VANNUCCHI, H.; ZUCOLOTO, S. & MARTINEZ, R. Experimental paracoccidioidomycosis in ethil alcohol-fed rats. Brazilian Joumal of Medical and Biological Research, Ribeirão Preto, v. 24, p. 901-907, 1991. GRAZZINELLI, R. T.; SILVA, M. E.; MORAES-SANTOS, T.; NICOLI; Jr. & VIEIRA, E.C. Effect of high sucrose diets on carcass composition in conventional and germfree mice. Archivos Latinoamericanos de Nutricion, Guatemala, v. 41, n. 4, p. 539-545, 1991. GRILLO, K. M.; TUCCI-VIEGAS, V.; SILVA, M. E.; SILVA, M. E. C.; FERREIRA, M. L. N.; PENA, F. G. & VIEIRA, E. C. Valor nutritivo de uma dieta de frango para uso em recuperação de crianças desnutridas. Revista Médica de Minas Gerais, Belo Horizonte, v. 2, n. 3, p. 140-142, 1992. IGUTI, M. I. & LAJOLO, F. M. Occurrence and purification of alphaamylase isoinhibitors in bean (Phaseolus vulgaris, L.) varieties. Joumal ofthe Agricultural and Food Chemistry, Washington, DC, V. 39, p. 2131-2136, 1991. ISHII, M. & ARAUJO, L. Uma proposta: otimização de programa de suplementação nutricional ao escolar e educação física. Revista Brasileira de Saúde Escolar, Campinas, v. 2, n. 3/4, p. 207-211, 1992. JAKABI, M. & FRANCO, B. D. G. M. Freqüência de isolamento de Escherichia coli enteropatogênica em alimentos de origem animal. Ciência e Tecnologia de Alimentos, Campinas, v. 11, n. 2, p. 170-181, 1991. KI, M.; SILVA, L. C.; MIYAMOTO, S.; KUBOTA, E. H. & SHIMOKOMAKI, M. Disulphide bonded collagens in shark (Prionace glauca) muscle. Comparative Biochemistry and Physiology, Southampton, v. 106, n. 2, p. 337-340, 1993. LAJOLO, F. M.; FINARDI FILHO, F. & MENEZES, E. W. Amylase inhibitors in Phaseolus vulgaris beans. Food Technology, Chicago, v. 45, n. 49, p. 119-121, 1991. ______ ; MARQUEZ, U.M.L. & FILISETTI-COZZI, T. M. C. C. Chemical composition and toxic compounds in rapesseed (Brassica napus, L.) cultivars grown in Brazil. Journal of the Agricultural and Food Chemistry, Washington, DC, v. 39, p.1933-1937, 1991. LANDGRAF, M.; IARIA, S. T. & FALCÃO, D. P. An improved enrichment procedure for the isolation of Yersinia enterocolítica and related species from milk. Journal of Food Protein, v. 56, n. 5, p. 477-450, 1993. LANFER MARQUEZ, U. M. & LAJOLO, F. M. ln vivo digestibility of bean (Phaseolus vulgaris, L.) proteins: the role of endogenous protein. Journal ofthe Agricultural and Food Chemistry, Washington, DC, v. 39, p. 1211-1215, 1991. ______; FILISETTI-COZZI, T. M. C. C. & LAJOLO, F. M. Nutritional value of rapesseds (Brassica napus, L.). Ciência e Tecnologia de Alimentos, Campinas, v.12, n.1, p. 52-61, 1991. LEI, D. L. M.; CHAVES, S. P.; STEFANINI, M. L. R.; LERNER, B. R. & ARRUDA, S.C. Estudo em escolares de Barueri (SP): estatura, rendimento escolar e suplementação alimentar. Revista de Nutrição da PUCCAMP, Campinas, v. 5, n. 1, p. 43-69, 1992. ______; _____ ; LERNER, B. R.; ARRUDA, S. C. & STEFANINI, M. L. R. Estudo em escolares de Barueri (SP): estatura, rendimento escolar e suplementação alimentar. Parte II: perfil de crescimento de crianças suplementadas. Revista de Nutrição da PUCCAMP, Campinas, v. 6, n. 1, p. 29-51, 1993. LERNER, B. R.; CHAVES, S. P.; LEI, D. L. M.; MONDINI, L. & STEFANINI, M. L. R. Perfil de crescimento de crianças matriculadas em programas de suplementação alimentar. Parte II: evolução do estado nutricional de desnutridos. Revista de Nutrição da PUCCAMP, Campinas, v, 4, n. 1/2, p. 93-109, 1991. LUZ, S. S.; SANTOS, S. & LANCHA JÚNIOR, A. H. Comportamento motor e estado nutricional em crianças de 7 a 11 anos de idade. Revista Paulista de Educação Física, São Paulo, v. 7, n. 1, p. 3-12, 1993. MACEDO DA COSTA, T.H. & DOREA, J.G. Concentrations of fat, protein, lactose and energy in milk of mothers using hormonal contraceptives. Annals of Tropical Paediatrics, Abingdon, v.12, p. 203-209, 1992. MARCHINI, J. S.; CASTILLO, L.; CHAPMAN, T. E.; VOGT, J. A.; AJAMI, A. & YOUNG, V. R. Phenylalanine conversion to tyrosine: comparative determination with L. Metabolism: Clinical and Experimental, Duluth, v. 42, p.1316-1322, 1993. _______; CORTIELLA, J.; HIRAMATSU, T.; CHAPMAN, T. E. & YOUNG, V. R. Requirements for indispensable amino acids in adult humans: longer-term amino acid rinetic study with support for the adequacy of the Massachusetts lnstitute of Technology amino acid requirement pattern. American Journal of Clinicai Nutrition, Bethesda, v. 58, p. 670-683, 1993. ___ ; UNAMUNO, M. R. L.; FONSECA, R. M. H. R.; RODRIGUES, M. M. P. & OUTRA DE OLIVEIRA, J. E. Métodos antropométricos para a avaliação do estado nutricional. Revista de Nutrição da PUCCAMP, Campinas, v. 5, n. 2, p. 121-142, 1992. MARQUEZ, U. M. L. & FILISETTI-COZZI, T. M. C. C. Chemical composition and toxic compounds in rapesseed (Brassica na pus, L.) cultivars growth in Brazil. Joumal ofthe Agricultural and Food Chemistry, Washington, DC, v.39, p.1933-1937, 1991. MARTINES, J. C.; REA, M. F. & DE ZOYSA, I. Breastfeeding in the first 6 months: no need for extra fluids. British Medical Joumal, London, v. 304, p.1068-1069, 1992. MARTINS, I. S.; COELHO, L. T., MAZZILI, R. N. SINGER, J. M.; SOUZA, C. U.; ANTONIETO JÚNIOR, A. E.; PASINI, U.; NIETO, R. A.; ALVARES, E. D. & OKANI, E.T. Doenças cardiovasculares arteroscleróticas, dislipidemias, hipertensão, obesidade e diabetes mellito em população da área metropolitana da região sudeste do Brasil. I: metodologia da pesquisa. Revista de Saúde Pública, São Paulo, v.27, p.250-261, 1993. MARTINS, R. L.; ATGIE, C.; GINESTEL, L.; NIBBELINK, M.; AMBID, L. & RICQUIER, D. lncreased GDP binding and thermogenic activity in brown adipose tissue mitochondria during arousal of the hibernating garden dormouse (Eliomysquercinus, L.) Comparative Biochemistry and Psysiology, v. 98A, n. 2, p. 311-316, 1991. MEIRELLES, R. J. A.; MEIRELLES, J. J. A.; TRICOLI, V. A. A. & MARQUES, J. L. Efeito de 3 meses de atividade física com controle alimentar em seis parâmetros sangüíneos em homens acima de 60 anos. Revista Brasileira de Ciência e Movimento, São Paulo, v. 5, n. 4, p. 47, 1991. MELO, M. S. O. & MANCINI FILHO, J. Antioxidantes naturais de castanha do Brasil (Bertholletia excelsa, H. B. R.). Ciência e Tecnologia de Alimentos, Campinas, v. 11, n. 2, p. 252-263, 1991. MONTEIRO, C. A. & TORRES, A. M. Can secular trends in child growth be estimulated from a single iron sectional survey? British Medical Journal, London, v. 305, p. 797-799, 1992. ____ ; BENÍCIO, M. H. D'A.; IUNES, R. F.; GOUVEIA, N. C.; TADDEI, J. A. A. C. & CARDOSO, M. A. A. Nutritional status of Brazilian children: trends from 1975 to 1989. Bulletin of the World Heaffh Organization, Geneva, v. 70, p. 657-666, 1992. ______; _______; _______; ________ ; &. ENDEF e PNSN: para onde caminha o crescimento da criança brasileira? Cadernos de Saúde Pública, Rio de Janeiro, v. 9, p. 85-95, 1993. MORAES-SANTOS, T.; NICOU, Jr.; SILVA, M. E. & VIEIRA, E. C. A method for steam-sterilizing semi-solid diets for germfree mice research. Archivos Latinoamericanos de Nutricion, Guatemala, v. 41, n. 3, p. 546-554, 1992. MORENO, F. S.; RIZZI, M. B. S. L.; DAGLI, M. L. Z. & PENTEADO, M.V.C. lnhibitory effects of beta-carotene on preneoplastic lesions induced in Wistar rats by the resistant hepatocyte model. Carcinogenesis, NewYork, v. 12, n.10, p. 1817-1822, 1991. MOURA, E. C.; CORRÊA, A. M. S. Normas para comercialização de alimentos para lactantes e responsabilidade das instituições de ensino. Revista de Nutrição da PUCCAMP, Campinas, v. 5, n. 1, p. 81-82, 1992. ______; LEONE, A. L.; BENTO, A. L. G.; LEONE, C. A. L.; SOUZA, I. C.; NEVES, J. F.; IMPROTA, M. T. W.; MILIORINI, M.; SORIANO, R. & BIANCHINI, S. Avaliação de um serviço básico de saúde: uma abordagem comunitária. Revista de Nutrição da PUCCAMP, Campinas, v. 5, n'. 2, p.101-120, 1992. _______; OLIVEIRA, R. B.; BASTOS, S. H. N.; SILVEIRA, S. F. & BITTAR, T. L. C. Prática de .aleitamento materno numa unidade da rede básica de saúde, Campinas, São Paulo. Alimentação e Nutrição, São Paulo, v. 12, n. 53, p. 43-36, 1992. ______; TAVARES, D. Q. ,& ROIG, S. M. Avaliação sensorial e metabólica de leite com baixo teor de lactose. Revista de Nutrição da PUCCAMP, Campinas, v. 6, n. 1, p. 9-28, 1993. MOURA, S. M.; DESTRO, M. T. & FRANCO, B. D. G. M. lncidence of Listeria species in raw and pasteurized milk prbduced in São Paulo, Brazil. lnternational Journal of Food Microbiology, Amsterdam, v. 19, p. 229-237, 1993. ________; ________; ________ BRANCACCIO, R. M. Low cost illumination system for Listeria spp research. Revista de Microbiologia, São Paulo, v. 22, n.1, p. 75-77, 1991. NASCIMENTO, D. Análise de risco e pontos críticos de controle de uma planta de processamento de alimentos (Restaurante Universitário/UFOP), em Ouro Preto. Boletim do Centro de Pesquisa e Processamento de Alimentos, Curitiba, v. 10, n. 2, p. 170, 1992. NÓBREGA, F. J.; BRASIL, A. L. D.; VÍTOLO, M. R. & LOPES, L. A. Estudo da influência do peso ao nascimento de variáveis maternas e sócio-econômicas na determinação da estatura em crianças. Jornal de Pediatria, Rio de Janeiro, v. 67, n. 3/4, p.163-167, 1991. ______ ; COSTA, M. C. O.; SOUZA QUEIROZ, S.; VÍTOLO, M. R. & SOLÉ, D. Estudo dei perfil lipídico y protéico dei colostro de madre adolescentes de reciém nascidos prematuros. Acta Pediatrica Espaflola, Madri, v. 50, p. 447-452, 1992. ___ ; VÍTOLO, M. R.; BRASIL, A. L. D. & LOPEZ, F. A. Condição nutricional de mães e filhos: relação com o peso de nascimento, variáveis maternas e sócio-econômicas. Jornal de Pediatria, Rio de Janeiro, v. 67, n. 9/10, p. 288-296, 1991. _____ &. Nutricional status of mothers and children: the relationship with birthweight, size of family and certain maternal variables. Children's Hospital Quartely, v. 4, n. 3, p.149-155, 1992. NOGUEIRA, N. N.; COLLI, C. & COZZOLINO, S. M. F. Biscoito fortificado com sangue bovino na dieta de pré-escolares. efeito no estado de nutrição em ferro; estudo preliminar. Cadernos de Saúde Pública, Rio de Janeiro, v. 8, n. 4, p. 270-286, 1992. OLIVEIRA, A. C.; DOREA, J. G.; DOMENE, S. M. O. Bibliometria na avaliação da produção científica da área de nutrição registrada no CIBRAN: período de 1984-1989. Ciência da Informação, Brasília, V. 21, n. 3, p. 239-242, 1992. _______ & JALALI, V. R. R. The use of -3H amino acids for the measurement of fecal endogenous nitrogen excreted by rats fed beandiets. Amino Acids, Vienna, v. 5, n. 1, p. 180-181, 1993. _____ & VIDAL, B. C. Type I collagen synthesis by rats fed beans (Phaseolus vulgaris, L) as the protein source. Brazilian Journal of Medical and Biological Research, Ribeirão Preto, v. 25, n. 5, p. 499-501, 1992. ORTEGA-FLORES, C. I. & PENTEADO, M. V. C. Carotenóides com atividade pró-vitamínica A em diferentes cultivares de mandioca (Manihot esculenta Crantz) do Estado de São Paulo. Revista de Farmácia e Bioquímica da Universidade de São Paulo, São Paulo, v. 28, n. 1, p. 51-60, 1992. PAINE, P. A.; DOREA, J. G.; PASQUALI, L. & MONTEIRO, A. M. Growth and cognition in Brazilian school chidren: a spntaneously occurring intervention study. lntemational Joumal of Behavioral Development, v.15, p.169-183, 1992. PANETTA, J. C.; ISHII, M. & BARROS, V. R. M. Propriedades dos leites "light" questão da qualidade da matéria-prima. Higiene Alimentar, São Paulo, v. 6, n. 23, p. 17-20, 1992. PAULA, C.R.; PURCHIO, A.; CORREA, B.; GAMBALE, W. & LANFER-MARQUEZ, U.M. A new medium for presumptive identification of Cryptococcus neoformans. Revista de Microbiologia, São Paulo, v. 23, n. 1, p. 51-53, 1992. PEDROSA, L. F. C. &COZZOLINO, S. M. F. Efeito de suplementação com ferro na biodisponibilidade de zinco em dieta regional no nordeste do Brasil. Revista de Saúde Pública, São Paulo, v. 27, n. 4, p. 266-270, 1992. PINTO, J. P. A. N. & PENTEADO, M. D. V. C. Vitamina A em fígados bovinos portadores de teleangiectasia capilar. Veterinária e Zootecnia, São Paulo, v. 5, p. 83-95, 1993. PINTO, R. M.; UNAMUNO, M. R. D. L.; RODRIGUES, M'. M. P. SANTOS, J. E.; MARCHINI, J. S. & OUTRA DE OLIVEIRA, J. E. Vitamin C load test in elderly subjects. Archivos Latinoamericanos de Nutrición, Guatemala, v. 43, n. 1, p. 20-22, 1993. PIZZINATTO, A. & SREBERNICH, S. M. A doença celíaca e a ingestão de produtos contendo trigo. Revista de Nutrição da PUCCAMP, Campinas, v. 5, n.1, p. 9-27, 1992. PRUDÊNCIO-FERREIRA, S. H. & ARÊAS, J. A. G. Effect of phospholipid on protein structure and solubility in the extrusion of lung proteins. FoodChemistry, Barking, v. 47, p.111-119, 1993. ______& _______ . Protein-protein inte-ractions in the extrusion of soya at various temperatures and moisture contents. Journal of Food Science, Chicago, v. 58, n. 2, p. 378-384, 1993. RAMALHO, R. A. G. & FLORES, H. Calorias e proteínas na etiologia da desnutrição experimental. Revista Clínica Pediátrica, v.17, p. 31,1993. RAMOS, K. S.; PESSA, R. P. & SANTOS, J. E. Osmolalidade e teor nitrogenado de dietas enterais industrializadas. Revista Brasileira de Nutrição Clínica, Porto Alegre, v. 6, n. 2, p. 7, 1991. REA, M.F. Breastfeeding promotion: the Brazilian experience. Nu Nytt Ulandhaiso-Vard, Uppsala, v. 5, n. 3, p.14-19, 1991. RODRIGUES, R. L. Influência de desnutrição energético-protéica na formação do calo ósseo: estudo histológico. Revista Brasileira de Ortopedia, São Paulo, v. 27, n. 6, p. 435-440, 1992. ___ & ZUCAS, S. M. Influência da desnutrição energético-protéica na formação do calo ósseo: estudo radiológico. Revista Brasileira de Ortopedia, São Paulo, v. 26, n. 3, p. 67-73, 1991. RONCADA, M. J. A missão do professor de primeiro grau na prevenção da hipovitaminose A. Revista Brasileira de Saúde Escolar, Campinas, v. 2, n. 3/4, p. 57-62, 1992. RONCADA, M. J.; OKANI, E. T. & VELASQUEZ, G. Efeito de alguns fatores físicos sobre a estabilidade de vitamina A e carotenóides plasmáticos. LAES/HAES, São Paulo, v. 13, n. 74, p. 4-6, 1992. SAKUMA, H. & FRANCO, B. D. G. M. Occurrence of Campylobacter jejuni and Campylobacter coliin retail rawchicken meat and giblets in São Paulo, Brazil. Revista de Microbiologia, São Paulo, v. 23, n.1, p.13-16, 1992. SANNAZZARO, C. A. C.; COELHO, L. T. & VELOSO, F. A. Novas tecnologias reduzen os custos e aumentam a produtividade do laboratório. LAES/HAES, São Paulo, v. 15, n. 85, p. 60-63, 1993. SANTOS, C. F.; SILVA, M. E. C.; SILVA, M. E.; NICOU JR.; CROCCO-AFONSO, L. C.; SANTOS, J. E.; BAMBIRRA,E. A. & VIEIRA, E. C. Effect of on essential fatty acid deficient diet on experimental infecction with Tripanosoma cruzi in germ-free and conventional mice. Brazilian Journal Medical Biological Research, Ribeirão Preto, v. 25, n. 8, p. 795-803, 1992. SANTOS, I. D. C.; OLIVEIRA, A. C.; VIDAL, B. C. Uso do colágeno na recuperação de ulcerações da mucosa duodenal de ratos induzidas por lectinas de feijão (Phaseolus vulgaris) cru. Caderno de Farmácia, Porto Alegre, v. 7, p. D13-D15, 1991. (suplemento). SANTOS, L. L.; TOSTA, C. E. & DOREA, J. G. Zinc reverts the increased sensitivity of lymphocytes from aged subjects to the antiproliferative effect of prostaglandin E2. Clinical lmmunology and lmmunopathology, New York, v. 64, p.184-187, 1992. SANTOS, R. C.; BRASILEIRO, G. F. & SILVA, M. E. Tumorigenicity of boiling water extract of broken fern Pteridium aquilinum. Ciência e Tecnologia de Alimentos, Campinas, v. 12, n. 1, p. 72-76, 1992. SILVA, M. L. P.; LAM-SANCHEZ, A.; ANDRADE, P.; PIMENTA, A.F. & OUTRA DE OLIVEIRA, J.E. Efeito da adubação nitrogenada sobre os teores de proteína e lisina, e taxa de eficiência protéica (PER) de grãos de milho opaco-2 e diversos estágios de maturação. Alimentos e Nutrição, Sã.o Paulo, v. 3, p. 1-9, 1991. SILVA, S. M. C. S.; KUGA, E. K. & MANCINI-FILHO, J. Efeito do processamento sobre ácidos graxos polinsaturados da fração lipídica da sardinha (Sardinella brasiliensis) e da tainha (Mugil cephalus). Revista de Farmácia e Bioquímica da Universidade de São Paulo, São Paulo, v. 29, n.1, p. 41-46, 1993. SINISTERRA-RODRIGUES, O. T.; SZARFARC, S. C. & BENÍCIO, M. H. D'A. Anemia e desnutrição maternas e sua relação com peso ao nascer. Revista de Saúde Pública, São Paulo, v. 25, p. 193-197, 1991. SOARES, S. E. & DELLA-MODESTA, R. C. & MANCINI-FILHO, J. Sensory detection limits of avocado oil in mixtures with olive oil. Revista Espaflola de Ciência y Tecnologia de Alimentos, v. 32, n. 5, p. 509-516, 1992. ___ & MANCINI FILHO, J. Ácido oxálico na clarificação de óleos de abacate. Boletim da Sociedade Brasileira de Ciência e Tecnologia de Alimentos, Rio de Janeiro, v. 26, n. 2, p. 97-103, 1992. _______; ______ TURATTI, J. M. & TANGO, J. S. Caracterização física, química e avaliação da estabilidade do óleo de abacate (Persea americana, Krill) nas diferentes etapas do processo de refino. Revista de Farmácia e Bioquímica da Universidade de São Paulo, São Paulo, v. 27, n. 1, p. 70-82, 1991. SOUZA, A. L. L.; MONEGO, E. T. JARDIM, P. C. B. V.; RAIMUNDO, M. S.; LOPES, C. E. M.; COELHO, J.; SANTOS, R.; GONDIN, M. R.; MARTINS, R. & DAHER, G. C. F. Uma experiência multiprofissional na abordagem do paciente hipertenso. Arquivos Brasileiros de Cardiologia, São Paulo, v. 59, n.1, p. 31-35, 1992. SREBERNICH, S. M. & PIZZINATTO, A. Proteína de soja como sucedâneo de ovos em macarrão. Revista de Nutrição da PUCCAMP, Campinas; v. 4, n. 1/2, p. 110-121, 1991. TASSINARI, A.; FRANCO, B. D. G. M. & LANDGRAF, M. An improved enrichment procedure for the isolation of Yersinia enterocolitica and related species from milk. Journal of Food Protein, v. 56, n. 5, p. 447-450, 1993. TENUTA-FILHO, A. Aspecto da utilização do krill antártico como alimento. Boletim da Sociedade Brasileira de Ciência e Tecnologia de Alimentos, Rio de Janeiro, v. 27, n. 1, p. 48-54, 1993. TERUYA, K. M.; MURAHOVSKY, J. & TOMA, T. S. Centro de lactação de Santos: promo·ção, treinamento e pesquisa em amamentação. Jornal de Pediatria, Rio de Janeiro, v. 68, n. 5/6, p. 186-188, 1992. TIRAPEGUI, J.; FUKUSHIMA, S. E. & GRIMALDI, G. Consideraciones sobre crecimiento y nutrición. Archivos Latinoamericanos de Nutrición, Guatemala, v. 43, p. 94-104, 1993. TRIGUEIRO, I. N. S. & PENTEADO, M. V. C. Teores de alfa e beta caroteno e atividade pró-vitamínica A de óleos de dendê brasileiros. Revista de Farmácia e Bioquímica da Universidade de São Paulo, São Paulo, v. 28, n. 1, p. 61-74, 1992. _____ & _______ . Mudanças nos_teores de alfa e beta caroteno em óleo de dendê durante o armazenamento à temperatura ambiente (26ºC). Boletim do Centro de Pesquisa e Processamento de Alimentos, Curitiba, v.11, n_1, p.1-10, 1993. ______&_______. Características físicas, químicas e estado de oxidação de óleos de dendê brasileiros. Boletim do Centro de Pesquisa e Processamento de Alimentos, Curitiba, v. 11, n. 2, p. 103-112, 1993. UNAMUNO, M. R. D. L.; OUTRA DE OLIVEIRA, J. E.; VANNUCCHI, H. & MARCHINI, J. S. Protein requirement assessmerit of ederly men on a rice and bean diet. Nutrition Research, Elmsford, v. 11, p. 149-157, 1991. VANNUCCHI, H. lnteraction of vitamins and minerais. Archivos Latinoamericànos de Nutrición, Guatemala, v. 41, n. 1, p. 8-18, 1991. ____ ; CUNHA, D. F.; OUTRA DE OLIVEIRA, J. E. & MARCHINI, J. S. Arm fat index as an alternative paramenter in the assessment of nutritional status of hospitalized patients. Journal of Nutritional Medicine, v. 3, p. 31-34, 1992. ____ & DUTRA DE OLIVEIRA, J. E. Problemas nutricionais da população urbana da região sudeste do Brasil. Archivos Latinoamericanos de Nutrición, Guatemala, v. 42, n. 4, p. 32-36, 1992. ______; MARCHINI, J. S.; FEN, L. F.; GARCIA, L. V.; CUNHA, D. F. & OUTRA DE OLIVEIRA, J. E. Dez anos de experiência em nutrição enteral monomérica. Medicina, Ribeirão Preto, v.24, n.3, p.165-174, 1991. ______; MORENO, F. S.; AMARANTE, A. R.; OUTRA DE OLIVEIRA, J. E. & MARCHINI, J. S. Plasma amino acid patterns in alcoholic pellagra patients. Alcohol & Alcoholism, Oxford, v. 10, n. 11, p. 431-436, 1991. VANNUCCHI, M. T. I.; VANNUCCHI, H.; HUMPHREY, M. Serum leveis of vitamin A and retinol bindind protein in chronic renal patients treated by continuous ambulatorial dialysis. lntemational Journal for Vitamin and Nutrition Research, Bem, v. 62, p. 107- 112, 1992. VÍTOLO, M. R.; BRASIL, A. L. D.; NÓBREGA, F. J. & ANCONA LOPEZ, F. Colostrum composition in adolescent mothers. Journal of the American of the College of Nutrition, New York, v. 12, n. 5, p. 547-550, 1993. YUYAMA, L.K.D.; FAVARO, R.M.D. YUYAMA, K. & VANNUCCHI, H. Bioavaibility of vitamin A from Peach Palm. Nutrition Research, Elmsford, v. 11, p. 1167-1175, 1991. ______; ROCHA, Y. R. & COZZOLINO, S. M. F. Análise química e percentual de adequação da dieta da região de Manaus, AM. Acta Amazônica, Manaus, v. 22, n. 4, p. 587-593, 1992.